Phylogenomics and mitochondrial genome evolution of the gall-associated doryctine wasp genera (Hymenoptera: Braconidae). Issue 8 (17th November 2019) - Samacá-Sáenz, Ernesto; Meza-Lázaro, Rubi N.; Branstetter, Michael G.; Zaldívar-Riverón, Alejandro
Abstract : The braconid subfamily Doryctinae is a cosmopolitan, highly diverse group of wasps mainly represented by parasitoid species. In this subfamily, however, there is a group of mainly Neotropical genera whose species are associated with galls of several vascular plant families. Previous molecular phylogenetic studies based on a few markers consistently recovered the monophyly of this group, though various relationships among genera and the monophyly of its most speciose genus, Allorhogas Gahan, remained unresolved. We characterized the mitogenomes of 13 representative species of the gall-associated doryctine clade and performed a phylogenomic analysis with both mitogenome and ultraconserved element (UCE) DNA sequence data to assess the classification of Doryctinae and to examine the evolution of phytophagy within the group. We found different patterns of tRNA gene rearrangements, two of which are present in most of the ingroup taxa. All phylogenetic analyses yielded highly similar, well-supported topologies that are congruent with relationships reported in previous studies. The resulting phylogenies confirmed Percnobracon as sister to the remaining genera and supported two separate clades whose genera are exclusively associated with Ficus (Moraceae). Allorhogas is confirmed to be polyphyletic. The combined evidence also supported a main Allorhogas clade composed of multiple phytophagous species that feed on at least five different host plant families. Further rearing records and phylogenetic studies are needed to examine host plant shifts and to broaden our understanding of a poorly studied radiation of gall-associated wasps.